Styrenic resin extrusion foam
The styrenic resin foam formulation addresses the balance of heat insulation, flame retardancy, and thermal stability by using specific ratios of heat radiation suppressors, epoxy compounds, and aliphatic bromine-containing polymers, ensuring effective performance and recyclability.
Patent Information
- Application Number
- JP2020176852
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-21
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-10-21
AI Technical Summary
Existing styrenic resin foams face challenges in achieving balanced heat insulation, flame retardancy, and thermal stability, particularly when incorporating heat radiation suppressants and epoxy compounds, which can degrade thermal stability and flame retardant performance.
A styrenic resin foam formulation containing 0.5 to 5.0 parts by weight of a heat radiation suppressor, 21 to 50 parts by weight of an epoxy compound as a stabilizer, and an aliphatic bromine-containing polymer as a flame retardant, along with additional stabilizers and blowing agents, to enhance thermal stability and flame retardancy while maintaining heat insulation.
The formulation achieves excellent heat insulation, flame retardancy, and thermal stability, with improved moldability and recyclability, passing combustion tests and maintaining molecular weight during recycling.
Smart Images

Figure 0007599306000001 
Figure 0007599306000002 
Figure 0007599306000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an extruded styrene-based resin foam. [Background technology]
[0002] Due to their excellent workability and heat insulating properties, extruded styrene resin foams are used, for example, as heat insulating materials for structures. In recent years, there has been an increasing demand for energy saving in houses and buildings, and there is a demand for technological development of foams with higher heat insulating properties than ever before.
[0003] Proposed examples of highly insulating foams include extruded styrene-based resin foams containing graphite or titanium oxide added within a prescribed range as a heat radiation inhibitor (see, for example, Patent Document 1), and extruded styrene-based resin foams using, as a foaming agent, environmentally friendly fluorinated olefins (hydrofluoroolefins and hydrochlorofluoroolefins) with an ozone depletion potential of zero and a small global warming potential, or alkyl chlorides such as methyl chloride and ethyl chloride (see, for example, Patent Documents 2 to 4).
[0004] On the other hand, brominated styrene-butadiene block copolymers have been proposed as flame retardants added to styrene-based resin extruded foams to impart flame retardancy to the extruded foams. However, brominated styrene-butadiene block copolymers have problems with thermal stability. Therefore, techniques have been proposed to improve the thermal stability of the brominated styrene-butadiene block copolymers themselves, and to improve the thermal stability by adding epoxy compounds (e.g., Patent Documents 5-6). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-221110 A [Patent Document 2] Special Publication No. 2008-546892 [Patent Document 3] JP 2019-189811 A [Patent Document 4] JP 2019-108416 A [Patent Document 5] International Publication No. 2007 / 058736 [Patent Document 6] International Publication No. 2010 / 080285 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide an extruded styrene-based resin foam having excellent heat insulating properties, flame retardancy and thermal stability. [Means for solving the problem]
[0007] In order to solve the above problems, the present inventors have conducted intensive research and found that when a thermal radiation inhibitor is added to a styrene-based resin foam to improve its heat insulation, the effect of improving the thermal stability by using an epoxy compound as a stabilizer in combination with an aliphatic bromine-containing polymer as a flame retardant is reduced. As a result of further investigation, the inventors have succeeded in producing a styrene-based resin foam having excellent heat insulation performance, flame retardancy, and thermal stability, and have arrived at the present invention. The present invention includes the following aspects. <1> An extruded styrene resin foam that satisfies the following (I) to (III): (I) containing 0.5 to 5.0 parts by weight of a heat radiation inhibitor based on 100 parts by weight of a styrene-based resin; (II) containing an aliphatic bromine-containing polymer as a flame retardant; (III) The composition contains, as a stabilizer, 21 to 50 parts by weight of (A) an epoxy compound based on 100 parts by weight of an aliphatic bromine-containing polymer. <2> The stabilizer is, for every 100 parts by weight of the aliphatic bromine-containing polymer, (B) 0 to 20 parts by weight of a polyhydric alcohol partial ester, (C) 4 to 20 parts by weight of a phenolic stabilizer, and (D) 0 to 0.9 parts by weight of a phosphite stabilizer Contains <1> The extruded styrene-based resin foam according to claim 1. <3> The epoxy compound includes at least one selected from the group consisting of bisphenol A diglycidyl ether type epoxy resins, cresol novolac type epoxy resins, and phenol novolac type epoxy resins. <1> or <2> The extruded styrene-based resin foam according to claim 1. <4> The stabilizer contains (B) a polyhydric alcohol partial ester, The polyhydric alcohol partial ester comprises a reaction product of dipentaerythritol and adipic acid. <1> ~ <3> 13. The extruded styrene-based resin foam according to claim 12. <5> The stabilizer contains (D) a phosphite stabilizer, The phosphite stabilizer includes at least one selected from the group consisting of 3,9-bis(2,4-di-tert-butylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, and tetrakis(2,4-di-tert-butyl-5-methylphenyl)-4,4'-biphenylene diphosphonite), <1> ~ <4> 13. The extruded styrene-based resin foam according to claim 12. <6> Further, the composition contains a phosphate ester. <1> ~ <5> 13. The extruded styrene-based resin foam according to claim 12. <7> The phosphate ester comprises tetrakis(2,6-dimethylphenyl)-m-phenylene bisphosphate. <6> The extruded styrene-based resin foam according to claim 1. <8> Contains hydrofluoroolefin and / or hydrochlorofluoroolefin as a blowing agent; <1> ~ <7> The extruded styrene-based resin foam according to any one of claims 1 to 7. <9> The hydrofluoroolefin and / or hydrochlorofluoroolefin is contained in an amount of 1.0 part by weight or more and 12.0 parts by weight or less relative to 100 parts by weight of the styrene-based resin. <8> The extruded styrene-based resin foam according to claim 1. <10> The heat radiation inhibitor contains graphite and / or titanium oxide. <1> ~ <9> The extruded styrene-based resin foam according to any one of claims 1 to 7. <11> The thermal conductivity of the extruded styrene-based resin foam is 0.0244 W / mK or less. <1> ~ <10> The extruded styrene-based resin foam according to any one of claims 1 to 7. <12> The density of the extruded styrene-based resin foam is 20 to 60 kg / m3. <1> ~ <11> The extruded styrene-based resin foam according to any one of claims 1 to 7. <13> The thickness of the styrene-based resin extruded foam is 10 mm or more and 150 mm or less. <1> ~ <12> The extruded styrene-based resin foam according to any one of claims 1 to 7. Effect of the Invention
[0008] The extruded styrene-based resin foam of the present invention can exhibit excellent heat insulating properties, flame retardancy, and thermal stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each configuration described below, and various modifications are possible within the scope of the claims. The technical scope of the present invention also includes embodiments and examples obtained by appropriately combining the technical means disclosed in different embodiments and examples. In addition, all academic literature and patent documents described in this specification are incorporated herein by reference. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more and B or less."
[0010] [1. Extruded styrene resin foam] The extruded styrene resin foam according to one embodiment of the present invention satisfies the following (I), (II), and (III). (I) containing 0.5 to 5.0 parts by weight of a heat radiation inhibitor per 100 parts by weight of a styrene-based resin; (II) containing an aliphatic bromine-containing polymer as a flame retardant; (III) The composition contains, as a stabilizer, 21 to 50 parts by weight of (A) an epoxy compound based on 100 parts by weight of an aliphatic bromine-containing polymer.
[0011] In the case where the styrene-based resin extruded foam contains an aliphatic bromine-containing polymer as a flame retardant, the epoxy compound is used in combination to improve the thermal stability. However, when the epoxy compound is added in excess, the stabilizing effect of the epoxy compound becomes excessive, and there is a problem that the flame retardant performance is reduced, so the epoxy compound is not usually used in an excessive amount. Even in the case of the styrene-based resin extruded foam having improved flame retardant performance and thermal stability, when a heat radiation inhibitor such as graphite or titanium oxide is added to reduce the thermal conductivity, the flame retardant tends to deteriorate more in the case where the graphite is added than in the case where the heat radiation inhibitor is not added. This is assumed to be because the thermal stability of the aliphatic bromine-containing polymer is further deteriorated by the impurities contained in the heat radiation inhibitor. As described above, the excessive addition of the epoxy compound usually causes a decrease in the flame retardant performance, but in the case where the heat radiation inhibitor is added, the decrease in the flame retardant performance is suppressed even if the amount of the epoxy compound added to the aliphatic bromine-containing polymer is more than the common amount. Specifically, by controlling the content of the epoxy compound to 21-50 parts by weight per 100 parts by weight of the aliphatic bromine-containing polymer, it is possible to achieve a good balance of thermal stability, flame retardancy, and heat insulation. For example, even when a styrene-based resin extrusion foam is recycled by reducing the volume thereof through heat shrinkage and / or thermal melting, it has good moldability and thermal stability that allows recycling. In addition, it passes the JIS A9511 combustion test method and / or exhibits flame retardancy with an oxygen index of 26% or more, and has excellent heat insulation.
[0012] (1-1. Styrene-based resin) vinegar As the styrene-based resin, one having an MFR of 0.1 to 50 g / 10 min is preferably used, because (i) it is excellent in molding processability during extrusion foaming, (ii) it is easy to adjust the discharge amount during molding, the thickness, width, apparent density, and closed cell ratio of the obtained styrene-based resin extruded foam to desired values, (iii) it is excellent in foamability (the thickness, width, apparent density, closed cell ratio, and surface property of the foam are easily adjusted to desired conditions), (iv) it is possible to obtain an extruded styrene-based resin foam with excellent appearance, and (v) it is possible to obtain an extruded styrene-based resin foam with a good balance of properties (for example, mechanical strength such as compressive strength, bending strength, or bending deflection amount, toughness, etc.). Furthermore, the MFR of the styrene-based resin is more preferably 0.3 to 30 g / 10 min, and particularly preferably 0.5 to 25 g / 10 min, from the viewpoint of the balance between molding processability and foamability, and mechanical strength and toughness. In one embodiment of the present invention, the MFR is measured according to JIS K7210 (1999) Method A and test condition H. .vinegar Styrene Resin teeth, polystyrene , resistance High impact polystyrene is preferred. From the economical point of view, polystyrene is particularly preferred. 。
[0013] (1-2. Flame retardants) The extruded styrenic resin foam of the present invention uses an aliphatic bromine-containing polymer as a flame retardant. Examples of the aliphatic bromine-containing polymer include brominated styrene-butadiene block copolymers, brominated styrene-butadiene random copolymers, brominated styrene-butadiene graft polymers, brominated butadiene polymers, and brominated-epoxidized styrene-butadiene block copolymers. These may be used alone or in combination of two or more. Among these, brominated styrene-butadiene block copolymers are preferred from the standpoints of performance, economy, and supply stability.
[0014] In one embodiment of the present invention, the content of the aliphatic bromine-containing polymer is preferably 0.5 to 10 parts by weight based on 100 parts by weight of the styrene-based resin, and in consideration of economic efficiency and the effects on other required physical properties, a more preferable range is 0.5 to 5 parts by weight.
[0015] In one embodiment of the present invention, other bromine-based flame retardants may be used in combination for the purpose of further improving flame retardant performance.
[0016] Specific examples of other bromine-based flame retardants include hexabromocyclododecane, tetrabromobisphenol A-bis(2,3-dibromo-2-methylpropyl)ether, tetrabromobisphenol A-bis(2,3-dibromopropyl)ether, and tris(2,3-dibromopropyl)isocyanurate. These may be used alone or in combination of two or more. Among these other bromine-based flame retardants, from the viewpoint of the flame retardant performance and thermal stability performance of the foam, a mixed bromine-based flame retardant consisting of tetrabromobisphenol A-bis(2,3-dibromo-2-methylpropyl)ether and tetrabromobisphenol A-bis(2,3-dibromopropyl)ether, and hexabromocyclododecane are preferred. The preferred amount of the other bromine-based flame retardant to be added is 0 to 3.0 parts by weight relative to 100 parts by weight of the styrene-based resin.
[0017] In one embodiment of the present invention, a radical generator can be used in combination with the styrene-based resin extrusion foam in order to improve the flame retardancy. Specific examples of the radical generator include 2,3-dimethyl-2,3-diphenylbutane, poly-1,4-diisopropylbenzene, 2,3-diethyl-2,3-diphenylbutane, 3,4-dimethyl-3,4-diphenylhexane, 3,4-diethyl-3,4-diphenylhexane, 2,4-diphenyl-4-methyl-1-pentene, and 2,4-diphenyl-4-ethyl-1-pentene. Peroxides such as dicumyl peroxide are also used. Among them, those stable under the resin processing temperature conditions are preferred, specifically 2,3-dimethyl-2,3-diphenylbutane and poly-1,4-diisopropylbenzene are preferred, and the preferred amount of the radical generator to be added is 0.05 to 0.8 parts by weight relative to 100 parts by weight of the styrene-based resin.
[0018] In one embodiment of the present invention, a phosphorus-based flame retardant such as a phosphoric acid ester or a phosphine oxide can be used in combination for the purpose of improving flame retardancy, in other words, as a flame retardant auxiliary, within a range that does not impair heat stability.
[0019] Examples of the phosphoric acid ester used in one embodiment of the present invention include condensed phosphoric acid esters such as triphenyl phosphate, tris(tributylbromoneopentyl)phosphate, tricresyl phosphate, trixylyleneyl phosphate, cresyl diphenyl phosphate, 2-ethylhexyl diphenyl phosphate, trimethyl phosphate, triethyl phosphate, tributyl phosphate, tris(2-ethylhexyl)phosphate, tris(butoxyethyl)phosphate, or tetrakis(2,6-dimethylphenyl)-m-phenylene bisphosphate. In addition, triphenylphosphine oxide is preferred as a phosphorus-based flame retardant of the phosphine oxide type. These phosphoric acid esters and phosphine oxides may be used alone or in combination of two or more. Among these phosphorus-based flame retardants, triphenyl phosphate, tris(tributylbromoneopentyl)phosphate, and tetrakis(2,6-dimethylphenyl)-m-phenylene bisphosphate are preferred, and tetrakis(2,6-dimethylphenyl)-m-phenylene bisphosphate is particularly preferred, from the viewpoint of the flame retardancy and thermal stability of the foam. The preferred amount of the phosphorus-based flame retardant to be added is 0.1 to 2 parts by weight per 100 parts by weight of the styrene-based resin.
[0020] (1-3. Stabilizer: (A) Epoxy Compound) In one embodiment of the present invention, by containing an epoxy compound as a stabilizer, it is possible to improve the thermal stability without impairing the flame retardant performance of the flame retardant.
[0021] As the epoxy compound used in one embodiment of the present invention, an epoxy compound generally used as a stabilizer for the aliphatic bromine-containing polymer can be used, and from the standpoints of cost, performance, and supply stability, it is preferable that the epoxy compound contains at least one selected from the group consisting of bisphenol A diglycidyl ether type epoxy resins, phenol novolac type epoxy resins, and phenol novolac type epoxy resins.
[0022] An example of the bisphenol A diglycidyl ether type epoxy resin is one represented by the following structural formula (1).
[0023] [ka]
[0024] An example of the cresol novolac type epoxy resin is represented by the following structural formula (2).
[0025] [ka]
[0026] An example of the phenol novolac type epoxy resin is represented by the following structural formula (3).
[0027] [ka]
[0028] In one embodiment of the present invention, an epoxy compound having a bromine atom added to a bisphenol A skeleton, as shown in the following structural formula (4), can also be used.
[0029] [ka]
[0030] These epoxy compounds may be used alone or in combination of two or more.
[0031] The epoxy compound used in one embodiment of the present invention preferably has an epoxy equivalent of less than 1000 g / eq. Since it is believed that the epoxy group inhibits the decomposition of the bromine-based flame retardant and improves the thermal stability of the styrene-based resin, if the epoxy equivalent is 1000 g / eq or more, the effect of inhibiting the decomposition of the flame retardant is very low, and as a result, a large amount needs to be added, which is not economically realistic. In consideration of the balance between cost and performance, it is more preferably less than 500 g / eq, and even more preferably less than 400 g / eq.
[0032] The content of the epoxy compound in the styrene-based resin extruded foam of the present invention is 21 to 50 parts by weight based on 100 parts by weight of the aliphatic bromine-containing polymer. From the viewpoint of economy and performance, it is preferably 25 to 50 parts by weight, more preferably 25 to 48 parts by weight, and even more preferably 25 to 47 parts by weight. If the content of the epoxy compound is less than 21 parts by weight, the stabilizing effect of the flame retardant is not fully exhibited, and the flame retardant and resin decompose, and the molecular weight of the resin tends to decrease, resulting in the bubble diameter of the bubbles forming the foam becoming enlarged, and the heat insulating performance tends to deteriorate. In addition, with the decrease in molecular weight distribution, the smoothness of the foam surface tends to deteriorate, and the moldability tends to deteriorate. Furthermore, the decomposition of the flame retardant causes other additives or resin to turn black, leading to poor appearance. In addition, even during recycling in which scraps generated during cutting of products are heated, melted, and kneaded, the decomposition of the flame retardant and resin tends to cause the resin to turn black and the molecular weight distribution to decrease, resulting in difficulty in recycling and increased costs. On the other hand, if the content of the epoxy compound exceeds 50 parts by weight, the stabilizing effect of the stabilizer becomes excessive, and the flame retardant cannot be effectively decomposed when the foam is burned, which tends to reduce the flame retardant performance.
[0033] (1-4. Stabilizer: (B) Polyhydric alcohol partial ester) In one embodiment of the present invention, the thermal stability of the flame retardant can be improved by using a polyhydric alcohol partial ester in combination as a stabilizer. In particular, even in the case of repeated recycling, decomposition of the resin and the flame retardant can be suppressed, thereby making it possible to obtain a foam having excellent moldability, flame retardancy, and heat insulation performance.
[0034] The polyhydric alcohol partial ester used in the present invention is a partial ester which is a reaction product of a polyhydric alcohol such as pentaerythritol, dipentaerythritol, tripentaerythritol, etc. with a monovalent carboxylic acid such as acetic acid, propionic acid, etc., or a divalent carboxylic acid such as adipic acid, glutamic acid, etc., and is a mixture of compounds having one or more hydroxyl groups in the molecule, and may contain a small amount of the raw material polyhydric alcohol. From the viewpoints of performance and economy, the polyhydric alcohol partial ester is preferably a partial ester which is a reaction product of dipentaerythritol and adipic acid, and an example of a commercially available product is Plainlyzer (registered trademark) ST-210 manufactured by Ajinomoto Fine-Techno Co., Ltd.
[0035] In one embodiment of the present invention, the content of the polyhydric alcohol partial ester is preferably 0 to 20 parts by weight, more preferably 0 to 17 parts by weight, based on 100 parts by weight of the aliphatic bromine-containing polymer. If the content of the polyhydric alcohol partial ester exceeds 20 parts by weight, the stabilizing effect is excessively exerted, which may reduce the flame retardant performance of the flame retardant itself.
[0036] (1-4. Stabilizers: (C) Phenol-based stabilizers) In one embodiment of the present invention, the thermal stability can be improved without impairing the flame retardant performance of the flame retardant by using a phenol-based stabilizer in combination.
[0037] The phenol-based stabilizer used in one embodiment of the present invention is not particularly limited, and commercially available substances can be used. Specific examples include triethylene glycol-bis-3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionate, pentaerythritol tetrakis[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate], and octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, which may be used alone or in combination of two or more. Among these, pentaerythritol tetrakis[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate] is preferably used in terms of cost and performance.
[0038] In one embodiment of the present invention, the content of the phenolic stabilizer is preferably 4 to 20 parts by weight, more preferably 5 to 20 parts by weight, based on 100 parts by weight of the aliphatic bromine-containing polymer. If the content of the phenolic stabilizer exceeds 20 parts by weight, it tends to affect the bubble formation of the foam, making it difficult to control the moldability and heat insulation. On the other hand, if the content of the phenolic stabilizer is less than 4 parts by weight, the stabilizing effect of the flame retardant may not be fully exhibited.
[0039] (1-5. Stabilizers: (D) Phosphite-based stabilizers) In one embodiment of the present invention, the thermal stability can be improved without impairing the flame retardant performance of the flame retardant by using a phosphite stabilizer in combination.
[0040] As the phosphite-based stabilizer used in one embodiment of the present invention, for example, 3,9-bis(2,4-di-tert-butylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, and tetrakis(2,4-di-tert-butyl-5-methylphenyl)-4,4'-biphenylene diphosphonite) are preferable since they do not deteriorate the flame retardant performance of the foam and improve the thermal stability of the foam.
[0041] In one embodiment of the present invention, the content of the phosphite-based stabilizer is preferably 0 to 0.9 parts by weight, more preferably 0 to 0.8 parts by weight, based on 100 parts by weight of the aliphatic bromine-containing polymer. If the content of the phosphite-based stabilizer exceeds 0.9 parts by weight, the stabilizing effect is exerted to a large extent, which may reduce the flame retardant performance of the flame retardant itself.
[0042] (1-6. Foaming agents) The blowing agent used in one embodiment of the present invention is not particularly limited, but in order to improve heat insulation, it is preferable to use hydrofluoroolefin and / or hydrochlorofluoroolefin (hereinafter, "hydrofluoroolefin and / or hydrochlorofluoroolefin" may be referred to as "hydro(chloro)fluoroolefin").
[0043] The hydrofluoroolefin used in the present invention is not particularly limited, but tetrafluoropropene is preferred from the viewpoint of low gas thermal conductivity and safety. Specific examples include trans-1,3,3,3-tetrafluoropropene (trans-HFO-1234ze), cis-1,3,3,3-tetrafluoropropene (cis-HFO-1234ze), and 2,3,3,3-tetrafluoropropene (trans-HFO-1234yf). The hydrochlorofluoroolefin used in the present invention is not particularly limited, but hydrochlorotrifluoropropene is preferred from the viewpoint of low gas thermal conductivity and safety. Specific examples include trans-1-chloro-3,3,3-trifluoropropene (trans-HCFO-1233zd). These hydrofluoroolefins and hydrochlorofluoroolefins may be used alone or in combination of two or more.
[0044] The content of the hydro(chloro)fluoroolefin according to one embodiment of the present invention is preferably 0.5 to 13.0 parts by weight, more preferably 1.0 to 12.0 parts by weight, and particularly preferably 1.5 to 11.0 parts by weight, relative to 100 parts by weight of the styrene-based resin. When the content of the hydro(chloro)fluoroolefin is less than 0.5 parts by weight relative to 100 parts by weight of the styrene-based resin, the effect of improving the heat insulating property by the hydro(chloro)fluoroolefin tends not to be expected. On the other hand, when the content of the hydro(chloro)fluoroolefin is more than 13.0 parts by weight relative to 100 parts by weight of the styrene-based resin, the hydro(chloro)fluoroolefin is separated from the resin melt during extrusion foaming, and spot holes (traces where a localized mass of the hydro(chloro)fluoroolefin breaks through the surface of the extruded foam and is released into the outside air) are generated on the surface of the extruded foam, or the closed cell ratio is reduced, which may impair the heat insulating property.
[0045] In the present invention, further, by using another foaming agent, a plasticizing effect and / or a co-foaming effect during foam production can be obtained, the extrusion pressure can be reduced, and a foam can be stably produced.
[0046] Other blowing agents include, for example, saturated hydrocarbons having 3 to 5 carbon atoms, such as propane, n-butane, i-butane, n-pentane, i-pentane, and neopentane; ethers, such as dimethyl ether, diethyl ether, methyl ethyl ether, isopropyl ether, n-butyl ether, diisopropyl ether, furan, furfural, 2-methylfuran, tetrahydrofuran, and tetrahydropyran; dimethyl ketone, methyl ethyl ketone, diethyl ketone, methyl-n-propyl ketone, methyl-n-butyl ketone, methyl-i-butyl ketone, methyl-n-amyl ketone, methyl-n-hexyl ketone, and ethyl-n-propyl ketone. Examples of the foaming agents that can be used include ketones such as ethyl n-butyl ketone and ethyl n-butyl ketone; saturated alcohols having 1 to 4 carbon atoms such as methanol, ethanol, propyl alcohol, i-propyl alcohol, butyl alcohol, i-butyl alcohol, and t-butyl alcohol; carboxylates such as methyl formate, ethyl formate, propyl formate, butyl formate, amyl formate, methyl propionate, and ethyl propionate; organic foaming agents such as alkyl halides such as methyl chloride and ethyl chloride; inorganic foaming agents such as water and carbon dioxide; and chemical foaming agents such as azo compounds and tetrazole. These other foaming agents may be used alone or in combination of two or more.
[0047] Among the other blowing agents, saturated alcohols having 1 to 4 carbon atoms, dimethyl ether, diethyl ether, methyl ethyl ether, methyl chloride, ethyl chloride, etc. are preferred from the viewpoints of foamability and foam moldability, etc., and water and carbon dioxide are preferred from the viewpoints of flammability of the blowing agent, flame retardancy or heat insulating properties of the foam, etc. Among these, dimethyl ether and ethyl chloride are preferred from the viewpoints of plasticizing effect, and water is particularly preferred from the viewpoints of economy and heat insulating improvement effect by controlling the bubble diameter.
[0048] In one embodiment of the present invention, when water and / or alcohols are used as the other blowing agent, it is preferable to add a water-absorbing substance in order to perform stable extrusion foam molding. Specific examples of the water-absorbing substance used in one embodiment of the present invention include water-absorbing polymers such as polyacrylate polymers, starch-acrylic acid graft copolymers, polyvinyl alcohol polymers, vinyl alcohol-acrylate copolymers, ethylene-vinyl alcohol copolymers, acrylonitrile-methyl methacrylate-butadiene copolymers, polyethylene oxide copolymers, and derivatives thereof, as well as fine powders having hydroxyl groups on the surface such as anhydrous silica (silicon oxide) having silanol groups on the surface [for example, AEROSIL manufactured by Nippon Aerosil Co., Ltd. is commercially available]; water-absorbing or water-swelling layered silicates such as smectite and swelling fluoromica, and their organically treated products; and porous substances such as zeolite, activated carbon, alumina, silica gel, porous glass, activated clay, diatomaceous earth, and bentonite. The content of the water-absorbing substance is appropriately adjusted by the amount of water and / or alcohols added, and is preferably 0.01 to 5 parts by weight, and more preferably 0.1 to 3 parts by weight, per 100 parts by weight of the styrene-based resin.
[0049] In the method for producing an extruded styrene resin foam according to one embodiment of the present invention, the pressure at which the foaming agent is added or injected is not particularly limited as long as it is higher than the internal pressure of an extruder or the like.
[0050] (1-7. Heat radiation suppressants) To the extruded styrene resin foam of the present invention, a heat radiation inhibitor is added in order to improve the heat insulating property.
[0051] The heat radiation inhibitor refers to a substance that has the properties of reflecting, scattering, and absorbing light in the near infrared or infrared region. By containing a heat radiation inhibitor, a foam having high heat insulation properties can be obtained. As the heat radiation inhibitor that can be used in the present invention, black particles such as graphite and carbon black, and white particles such as titanium oxide, barium sulfate, zinc oxide, aluminum oxide, and antimony oxide can be used. These may be used alone or in combination of two or more. From the viewpoint of a large heat radiation inhibitory effect, graphite, titanium oxide, and barium sulfate are preferred, and it is more preferred to contain graphite and / or titanium oxide.
[0052] Examples of graphite include scaly (flake) graphite, amorphous graphite, spherical graphite, and artificial graphite. Among these, it is preferable to use graphite whose main component is scaly (flake) graphite, because it has a high heat radiation suppression effect. Graphite preferably has a fixed carbon content of 80% or more, and more preferably 85% or more. By setting the fixed carbon content within the above range, a foam having high heat insulation properties can be obtained.
[0053] The average particle size of the graphite is preferably 15 μm or less, more preferably 10 μm or less. By setting the average particle size within the above range, the specific surface area of the graphite increases, and the probability of collision with heat radiation increases, thereby enhancing the heat radiation suppression effect. The average particle size means the particle size at which the cumulative volume of the total particle volume is 50% (volume average particle size by laser diffraction scattering method) when the particle size distribution is measured and analyzed by a laser diffraction scattering method based on the Mie theory in accordance with ISO13320:2009 and JIS Z8825:2013.
[0054] Examples of titanium oxide include general rutile type titanium oxide and anatase type titanium oxide, as well as conductive rutile type titanium oxide and conductive anatase type titanium oxide which have been imparted with electrical conductivity.
[0055] The average particle size of the white particles is not particularly limited, but in consideration of effectively reflecting infrared rays and coloring to resin, for example, in the case of titanium oxide, it is preferably 0.1 μm to 10 μm, and more preferably 0.15 μm to 5 μm.
[0056] In one embodiment of the present invention, the content of the heat radiation inhibitor is 0.5 parts by weight or more and 5.0 parts by weight or less, more preferably 1.0 parts by weight or more and 4.5 parts by weight or less, and even more preferably 1.0 parts by weight or more and 4.0 parts by weight or less, relative to 100 parts by weight of the styrene-based resin. If the content is less than 0.5 parts by weight, a sufficient heat radiation suppression effect cannot be obtained. On the other hand, if the content exceeds 5.0 parts by weight, the heat radiation suppression effect corresponding to the content cannot be obtained, and there is no cost advantage.
[0057] (1-8. Moldability improver) In one embodiment of the present invention, a polyhydric alcohol fatty acid ester and / or polyethylene glycol may be added as a moldability improver, if necessary. The use of these can impart a beautiful surface to the extruded foam and increase the thickness of the extruded foam (i.e., improve the moldability of the extruded foam).
[0058] Examples of the polyhydric alcohol fatty acid ester used in one embodiment of the present invention include esters of higher fatty acids having 10 to 24 carbon atoms and polyhydric alcohols such as ethylene glycol, glycerin, 1,2,4-butanetriol, diglycerin, pentaerythritol, sorbitol, erythritol, hexanetriol, etc. These polyhydric alcohol fatty acid esters may be used alone or in combination of two or more kinds.
[0059] Among these, glycerin fatty acid esters, particularly mono-, di-, tri- or tetra-fatty acid esters of glycerin are preferred from the standpoints of availability, cost, etc.
[0060] As the glycerol fatty acid ester, it is preferable to use at least one selected from the group consisting of, for example, lauric acid monoglyceride, lauric acid diglyceride, lauric acid triglyceride, palmitic acid monoglyceride, palmitic acid diglyceride, palmitic acid triglyceride, stearic acid monoglyceride, stearic acid diglyceride, stearic acid triglyceride, and stearic acid tetraglyceride.
[0061] The melting point of the glycerin fatty acid ester used in the present invention is preferably 150° C. or less, more preferably 130° C. or less, and particularly preferably 110° C. When the melting point of the glycerin fatty acid ester is 150° C. or less, it is excellent in handleability, for example, in a dry blending step during the production of an extruded foam, and since it exists as a liquid during extrusion foam molding, it can also impart a plasticizing effect to the styrene-based resin during extrusion foam molding, so that it can exhibit a sufficient thickening effect of the extruded styrene-based resin foam. On the other hand, when the melting point is higher than 150° C., it exists as a solid during extrusion foam molding, and it cannot impart a plasticizing effect to the styrene-based resin during extrusion foam molding, so that it may not be possible to exhibit a sufficient thickening effect of the extruded styrene-based resin foam.
[0062] The content of the polyhydric alcohol fatty acid ester used in one embodiment of the present invention is preferably 0.05 parts by weight or more and 5.0 parts by weight or less, more preferably 0.1 parts by weight or more and 3.0 parts by weight or less, and particularly preferably 0.5 parts by weight or more and less than 2.0 parts by weight, based on 100 parts by weight of the styrene-based resin. If the content of the polyhydric alcohol fatty acid ester is less than 0.05 parts by weight, the effect of thickening the extruded foam tends to be insufficient. On the other hand, if it exceeds 5.0 parts by weight, the excessive amount may impair extrusion, foaming, and molding stability during production, or may deteriorate various properties such as heat resistance of the extruded foam.
[0063] The average molecular weight of the polyethylene glycol used in one embodiment of the present invention is not particularly limited, but is preferably from 1000 to 25000, more preferably from 1500 to 20000, and particularly preferably from 3000 to 15000. These polyethylene glycols having different average molecular weights may be used alone or in combination of two or more. When the molecular weight of the polyethylene glycol is from 1000 to 25000, the freezing point of the polyethylene glycol is higher than room temperature and the polyethylene glycol is in a solid state at room temperature, so that depending on the amount used, the polyethylene glycol has excellent handleability in, for example, a dry blending step during the production of an extruded foam, does not bleed out from the inside of the extruded foam to the surface, and has a freezing point lower than the extrusion foaming temperature, and can impart a plasticizing effect to the styrene-based resin during extrusion foaming, so that the polyethylene glycol can exert a sufficient effect of imparting surface properties to the styrene-based resin extruded foam and a sufficient effect of adding thickness.
[0064] The content of polyethylene glycol in one embodiment of the present invention is preferably 0.05 parts by weight or more and 5.0 parts by weight or less, more preferably 0.1 parts by weight or more and 3.0 parts by weight or less, and particularly preferably 0.2 parts by weight or more and 1.0 parts by weight or less, relative to 100 parts by weight of the styrene-based resin. If the content of polyethylene glycol is less than 0.05 parts by weight, the surface property imparting effect and the thickness-imparting effect tend to be insufficient. On the other hand, if the content of polyethylene glycol is more than 5.0 parts by weight, the content of polyethylene glycol is excessive, and therefore there is a risk of impairing the extrudability, foamability, and molding stability during production, or of deteriorating various properties such as the heat resistance of the extruded foam.
[0065] In one embodiment of the present invention, when polyethylene glycol and polyhydric alcohol fatty acid ester are used in combination as a moldability improving agent, the total amount of polyethylene glycol and polyhydric alcohol fatty acid ester is preferably 0.05 parts by weight or more and 5.0 parts by weight or less, more preferably 0.1 parts by weight or more and 3.0 parts by weight or less, and particularly preferably 0.2 parts by weight or more and 2.0 parts by weight or less, relative to 100 parts by weight of styrene-based resin. If the content is less than 0.05 parts by weight, the surface property imparting effect and the thickness-imparting effect tend to be insufficient. On the other hand, if the content is more than 5.0 parts by weight, the content is excessive, which may impair extrudability, foamability, and molding stability during production, or may deteriorate various properties such as heat resistance of the extruded foam.
[0066] (1-9. Other additives) In one embodiment of the present invention, further, as necessary, additives such as inorganic compounds such as silica, calcium silicate, wollastonite, kaolin, clay, mica, calcium carbonate, sodium stearate, calcium stearate, magnesium stearate, barium stearate, liquid paraffin, olefin wax, stearylamide compounds, phenolic antioxidants, phosphorus stabilizers, nitrogen stabilizers, sulfur stabilizers, light resistance stabilizers such as benzotriazoles and hindered amines, bubble size regulators such as talc, flame retardants other than the above, antistatic agents, colorants such as pigments, and plasticizers may be contained in the styrene resin, as long as the effects of one embodiment of the present invention are not impaired. In addition, as necessary, other resins may be used in combination with the styrene resin, as long as the effects of one embodiment of the present invention are not impaired.
[0067] (1-8. Physical Properties) The thermal conductivity of the styrene-based resin extruded foam according to one embodiment of the present invention is not particularly limited, but from the viewpoint of thermal insulation considering that the foam functions, for example, as a thermal insulation material for building, or as a thermal insulation material for refrigerators or refrigerated vehicles, the thermal conductivity measured at an average temperature of 23°C one week after production is preferably 0.0284 W / mK or less, more preferably 0.0244 W / mK or less, and particularly preferably 0.0224 W / mK or less.
[0068] The apparent density of the extruded styrene-based resin foam according to one embodiment of the present invention is, for example, 20 kg / m from the viewpoint of heat insulation and light weight in consideration of its function as a heat insulating material for buildings, or a heat insulating material for refrigerators or refrigerated vehicles. 3 More than 60kg / m 3 It is preferable that the thickness is 25 kg / m or less, and more preferable that the thickness is 25 kg / m 3 More than 40kg / m 3 The following is the result.
[0069] The closed cell ratio of the extruded styrene-based resin foam according to one embodiment of the present invention is preferably 90% or more, more preferably 95% or more. If the closed cell ratio is less than 90%, the foaming agent will dissipate from the extruded foam early, resulting in a decrease in heat insulation.
[0070] The average bubble diameter in the thickness direction of the styrene-based resin extruded foam according to one embodiment of the present invention is preferably 0.05 mm or more and 0.5 mm or less, more preferably 0.05 mm or more and 0.4 mm or less, and particularly preferably 0.05 mm or more and 0.3 mm or less. In general, the smaller the average bubble diameter, the shorter the distance between the bubble walls of the foam, so that the range of movement of the bubbles of the extruded foam when shaping the extruded foam during extrusion foaming is narrow, making deformation difficult, and it tends to be difficult to impart a beautiful surface to the extruded foam and to produce a thickness of the extruded foam. When the average bubble diameter in the thickness direction of the styrene-based resin extruded foam is smaller than 0.05 mm, it becomes particularly difficult to impart a beautiful surface to the extruded foam and to produce a thickness of the extruded foam. On the other hand, when the average bubble diameter in the thickness direction of the styrene-based resin extruded foam exceeds 0.5 mm, there is a risk that sufficient heat insulation cannot be obtained.
[0071] The average cell diameter of the extruded styrene resin foam according to one embodiment of the present invention can be evaluated as follows using a microscope (DIGITAL MICROSCOPE VHX-900, manufactured by KEYENCE CORPORATION).
[0072] The obtained styrene-based resin extruded foam was observed from the extrusion direction at a widthwise center and at a location 150 mm from one end in the widthwise direction to the opposite end (the same location for both ends in the widthwise direction) at three locations in total at the center in the thickness direction, using the microscope, and a 100x magnified photograph was taken. Similarly, the extrusion direction vertical cross sections at the center in the thickness direction at three locations in the width direction were observed from the width direction using the microscope, and a 100x magnified photograph was taken. Three 2 mm straight lines were drawn arbitrarily in the thickness direction of the magnified photograph (three lines for each observation location and each observation direction), and the number a of bubbles in contact with the straight lines was measured. From the measured number a of bubbles, the average bubble diameter A in the thickness direction for each observation location was calculated by the following formula (1). The average value of the three locations (two directions at each location) was taken as the average bubble diameter A (average value) in the thickness direction of the styrene-based resin extruded foam.
[0073] Average bubble diameter A (mm) in the thickness direction at each observation point = 2 × 3 / number of bubbles a ···(1).
[0074] The cross sections perpendicular to the extrusion direction of the obtained styrene-based resin extruded foam at the center in the width direction and at a location 150 mm from one end in the width direction to the opposite end (the same location for both ends in the width direction) were observed from the width direction using the microscope, and 100x magnified photographs were taken. Three 2 mm straight lines were drawn in the extrusion direction of the enlarged photograph (three lines for each observation location), and the number b of bubbles in contact with the straight lines was measured. From the measured number b of bubbles, the average bubble diameter B in the extrusion direction for each observation location was calculated using the following formula (2). The average value of the three locations was taken as the average bubble diameter B (average value) in the extrusion direction of the styrene-based resin extruded foam.
[0075] Average bubble diameter in the extrusion direction at each observation point B (mm) = 2 × 3 / number of bubbles b (2).
[0076] The obtained styrene-based resin extruded foam was observed from the extrusion direction at a total of three locations, namely, the widthwise center and a location 150 mm from one end in the widthwise direction to the opposite end (the same location for both ends in the widthwise direction), in a widthwise vertical cross section, and a 100x magnified photograph was taken. Three 2 mm straight lines were drawn at random in the widthwise direction of the enlarged photograph (three lines for each observation location), and the number c of bubbles in contact with the straight lines was measured. From the measured number c of bubbles, the average cell diameter C in the width direction for each observation location was calculated by the following formula (3). The average value of the three locations was taken as the average cell diameter C (average value) in the width direction of the styrene-based resin extruded foam.
[0077] Average bubble diameter C (mm) in the width direction at each observation point = 2 × 3 / number of bubbles c (3).
[0078] The cell deformation ratio of the extruded styrene-based resin foam according to one embodiment of the present invention is preferably 0.7 to 2.0, more preferably 0.8 to 1.5, and even more preferably 0.8 to 1.2. If the cell deformation ratio is less than 0.7, the compressive strength is low, and the extruded foam may not have a strength suitable for the intended use. In addition, the cells tend to return to a spherical shape, and the extruded foam tends to have poor dimensional (shape) retention. On the other hand, if the cell deformation ratio exceeds 2.0, the number of cells in the thickness direction of the extruded foam is reduced, and the effect of improving the heat insulation due to the cell shape is reduced.
[0079] The cell deformation ratio of the extruded styrene resin foam according to one embodiment of the present invention can be calculated from the above-mentioned average cell diameter by the following formula (4).
[0080] Bubble deformation rate (unitless) = A (average value) / {〔B (average value) + C (average value)〕 / 2} (4).
[0081] The thickness of the extruded styrene resin foam according to one embodiment of the present invention is preferably from 10 mm to 150 mm, more preferably from 20 mm to 130 mm, and particularly preferably from 30 mm to 120 mm, from the viewpoints of thermal insulation, bending strength, and compressive strength in consideration of its function as, for example, a thermal insulation material for buildings, or a thermal insulation material for refrigerators or refrigerated vehicles.
[0082] As described in the examples and comparative examples of the present invention, in the case of an extruded styrene resin foam, after it is shaped by extrusion foaming, both surfaces of a plane perpendicular to the thickness direction may be cut to a depth of about 5 mm on each side in the thickness direction to obtain the product thickness. However, unless otherwise specified, the thickness of the extruded styrene resin foam according to one embodiment of the present invention refers to the uncut thickness after it has been shaped by extrusion foaming.
[0083] Thus, according to one embodiment of the present invention, it is possible to easily obtain an extruded styrene-based resin foam having excellent heat insulating properties and flame retardancy, a beautiful appearance, and a sufficient thickness suitable for use.
[0084] 2. Method for producing extruded styrene resin foam The method for producing a styrene-based resin extrusion foam according to one embodiment of the present invention includes a melting step in which a resin composition containing a styrene-based resin, a heat radiation inhibitor, a flame retardant, and a stabilizer is heated and melted in an extruder equipped with a die slit section, and a foaming agent is added to prepare a foamable melt, and a foaming step in which the foamable melt obtained in the melting step is extruded from the die slit section into a low pressure region to foam, the flame retardant containing an aliphatic bromine-containing polymer, the stabilizer containing an epoxy compound, and the resin composition containing 21 to 50 parts by weight of the epoxy compound per 100 parts by weight of the aliphatic bromine-containing polymer. The configuration already described in [1. Styrene-based resin extrusion foam] is used by reference, and the description thereof is omitted here.
[0085] As an example of a method for producing a styrene-based resin extrusion foam, the following method can be mentioned. First, a styrene-based resin, a radiation suppressant, a flame retardant, a stabilizer, and, if necessary, the above-mentioned various additives are supplied to a heat-melting section of an extruder having a die slit section (in other words, a resin composition is supplied to the heat-melting section of an extruder). At this time, a foaming agent can be mixed into the resin composition under high pressure conditions at any stage (for example, before the resin composition is heated and melted, during the resin composition is heated and melted, or after the resin composition is heated and melted). Then, the resin composition is made into a fluid gel. The above is the melting process. Thereafter, the foamable molten material obtained in the melting step is cooled to a temperature suitable for extrusion foaming, and then the fluid gel is extruded through a die slit into a low pressure region (e.g., an atmospheric pressure region) to form an extruded styrene resin foam. This is the foaming step.
[0086] In the melting step, examples of the method for blending various additives with the styrene-based resin include a method for adding various additives to the styrene-based resin and mixing them by dry blending; a method for adding various additives to the molten styrene-based resin from a supply section provided midway through the extruder; a method for preparing a master batch in which various additives are incorporated into the styrene-based resin at a high concentration using an extruder, kneader, Banbury mixer, rolls or the like, and mixing the master batch with the styrene-based resin by dry blending; and a method for supplying various additives to the extruder using supply equipment separate from the styrene-based resin.
[0087] The heating temperature in the heat melting section is equal to or higher than the temperature at which the styrene resin used melts. The heating temperature is preferably a temperature (for example, about 150°C to 260°C) at which molecular deterioration of the resin due to the influence of additives and the like is suppressed as much as possible. The melt kneading time in the heat melting section cannot be uniquely defined because it varies depending on the extrusion amount of the styrene resin per unit time and / or the type of extruder used as the heat melting section and as the melt kneading section, and can be appropriately set as the time required for the styrene resin, the foaming agent, and the additives to be uniformly dispersed and mixed.
[0088] As the melt-kneading section, a mechanism used in normal extrusion foaming can be used without any particular limitation, and examples thereof include a screw-type extruder.
[0089] The pressure at which the foaming agent is added or injected is not particularly limited, and may be any pressure higher than the internal pressure of an extruder or the like.
[0090] In the foaming step, the method of extrusion foaming may be, for example, a method in which the above-mentioned fluid gel is released from a high pressure region to a low pressure region through a die slit portion having a straight slit shape used for extrusion molding. In this way, an extruded foam is obtained. Note that the shape of the die slit portion is not particularly limited, and various die slit portions in the technical field can be used.
[0091] In the foaming step, the foaming pressure in the extrusion foaming (in other words, the pressure applied to the foamable molten material before (for example, immediately before) it is extruded through the die slit) is preferably 3.5 MPa or more and 10.0 MPa or less, more preferably 3.5 MPa or more and 8.0 MPa or less, and even more preferably 3.5 MPa or more and 6.0 MPa or less. When the foaming pressure is within this range, an advantageous effect of reducing the thin skin ratio of the extruded styrene resin foam can be obtained. The foaming pressure can be adjusted by adjusting the opening of the slit in the die slit section and / or the temperature of the die slit section.
[0092] The extruded styrene resin foam may be molded into a plate-like foam, i.e., an extruded foam plate. For example, the extruded foam obtained as described above can be molded into a plate-like foam having a large cross-sectional area by using a molding die installed in close contact with or in contact with a slit die and a molding roll installed adjacent to the downstream side of the molding die. The desired cross-sectional shape, surface properties, and quality of the foam can be obtained by adjusting the flow surface shape of the molding die and the die temperature. EXAMPLES
[0093] Examples of the present invention will be described below, but the present invention is not limited to these.
[0094] [Raw materials] The raw materials used in the examples and comparative examples are as follows. ○Base resin Styrene-based resin A [PS Japan Co., Ltd., G9401; MFR 2.2g / 10min] Styrene-based resin B [PS Japan Co., Ltd., 680; MFR 7.0g / 10min] ○Heat radiation suppressant Graphite [Marutoyo Foundry Manufacturing Co., Ltd., M-885; flake graphite, average particle size 5.5 μm, fixed carbon content 89%] Titanium oxide [(Sakai Chemical Industry Co., Ltd., R-7E; average particle size 0.23 μm] ○Flame retardants Brominated styrene-butadiene block copolymer [Chemtura, EMERALD INNOVATION #3000] ○Stabilizer (A) Epoxy compounds Bisphenol-A glycidyl ether [ADEKA Corporation, EP-13] · Cresol novolac epoxy resin [DIC Corporation, EPICLON N-680] Stabilizer (B) Polyhydric alcohol partial ester Dipentaerythritol-adipic acid reaction mixture [Ajinomoto Fine-Techno Co., Ltd., Plain Riser ST210] ○Stabilizers (C) Phenol-based stabilizers Pentaerythritol tetrakis[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate][ANOX20 manufactured by Chemtura] ○Stabilizers (D) Phosphite stabilizers 3,9-bis(2,4-di-tert-butylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane (Ultranox® 626, manufactured by Chemtura) Flame retardant assistant Condensed phosphate ester (tetrakis(2,6-dimethylphenyl)-m-phenylene bisphosphate) [PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.] Radical generator ·Poly-1,4-diisopropylbenzene [United Initiators, CUROX CC-P3]. Other additives Talc [Talc Powder PK-Z, manufactured by Hayashi Kasei Co., Ltd.] Calcium stearate [Sakai Chemical Industry Co., Ltd., SC-P] Bentonite [Hojun Co., Ltd., Bengelbright 11K] Silica [Evonik Degussa Japan Co., Ltd., Carplex BS-304F] Ethylene bis stearic acid amide [NOF Corp., Alflow H-50S] Stearic acid monoglyceride [Riken Vitamin Co., Ltd., Rikemal S-100P] ○Foaming agent · HFO-1234ze [Honeywell Japan Co., Ltd.] ·HCFO-1233zd [Honeywell Japan Co., Ltd.] Isobutane [Mitsui Chemicals, Inc.] Dimethyl ether [Mitsui Chemicals, Inc.] Ethyl chloride [Nippon Specialty Chemical Industry Co., Ltd.] Water [Settsu City, Osaka Prefecture tap water]
[0095] [Measurement method] In the examples and comparative examples, various parameters were measured and evaluated according to the following measurement methods.
[0096] (1) Apparent density (kg / m3) The weight of the resulting extruded styrene resin foam was measured, and the length, width and thickness of the foam were also measured. From the measured weight and each dimension, the apparent density of the extruded styrene resin foam was calculated based on the following formula. The unit of apparent density was then expressed as kg / m 3 was converted to. Apparent density (g / cm 3 ) = foam weight (g) / foam volume (cm 3 ).
[0097] (2) Closed cell ratio Test pieces measuring 40 mm thick, 25 mm long (in the extrusion direction), and 25 mm wide were cut out from three locations of the obtained extruded styrene foam: the widthwise center, a location 150 mm from one end in the widthwise direction toward the opposite end, and a location 150 mm from the other end in the widthwise direction toward the opposite end. The test pieces were measured according to procedure C of ASTM-D2856-70, and the closed cell ratio of each test piece was calculated by the following formula. The average value of the closed cell ratios at the three locations was taken as the closed cell ratio of the extruded styrene foam. Closed cell ratio (%)=(V1-W / ρ)×100 / (V2-W / ρ) Here, V1(cm 3 ) is the true volume of the test piece (excluding the volume of the part that is not an independent bubble) measured using an air comparison type specific gravity meter [Tokyo Science Co., Ltd., air comparison type specific gravity meter, Model 1000]. V2 (cm 3 ) is the apparent volume calculated from the outer dimensions of the test piece measured using a vernier caliper [Mitutoyo Corporation, M-type standard vernier caliper N30]. W (g) is the total weight of the test piece. Also, ρ (g / cm 3 ) is the density of the styrene resin that constitutes the extruded foam, and is 1.05 (g / cm 3 ) was decided.
[0098] (3) Average bubble diameter and bubble deformation rate in the thickness direction For the obtained extruded styrene resin foam, the average cell diameter in the thickness direction and the cell deformation rate were determined using a microscope [DIGITAL MICROSCOPE VHX-900, manufactured by KEYENCE CORPORATION] as described above.
[0099] (4) HFO-1234ze / HCFO-1233zd content per 100 g of styrene-based resin in extruded foam The obtained styrene-based resin extruded foam was allowed to stand under the conditions of standard temperature condition class 3 (23°C ± 5°C) and standard humidity condition class 3 (50 + 20, -10% RH) specified in JIS K 7100, and the HFO-1234ze / HCFO-1233zd content 7 days after production was evaluated using the following equipment and procedures. a) Equipment used: Gas chromatograph GC-2014 [manufactured by Shimadzu Corporation] b) Column used: G-Column G-950 25UM [manufactured by Chemicals Evaluation and Research Institute, Japan] c) Measurement conditions; ·Inlet temperature: 65℃ Column temperature: 80℃ Detector temperature: 100℃ Carrying gas: High purity helium Carry gas flow rate: 30mL / min Detector: TCD ·Current: 120mA A test piece of about 1.2 g (depending on the apparent density) cut from the foam was placed in a sealable glass container of about 130 cc (hereinafter referred to as "sealed container"), and the air in the sealed container was removed using a vacuum pump. The sealed container was then heated at 170°C for 10 minutes, and the foaming agent in the foam was taken out into the sealed container. After the sealed container returned to room temperature, helium was introduced into the sealed container to return it to atmospheric pressure, and 40 μL of a mixed gas containing HFO-1234ze / HCFO-1233zd was taken out using a microsyringe, and evaluation was performed using the above-mentioned a) to c) equipment and measurement conditions.
[0100] (5) Thermal conductivity In accordance with JIS A 9521, a test piece of 50 mm thickness × 300 mm length (extrusion direction) × 300 mm width cut from a styrene-based resin extruded foam was used to measure thermal conductivity at an average temperature of 23°C using a thermal conductivity measuring device [Eiko Seiki Co., Ltd., HC-074]. Specifically, after the production of the styrene-based resin extruded foam, a test piece of the above dimensions was cut out and left to stand under standard temperature condition class 3 (23°C ± 5°C) and standard humidity condition class 3 (50 + 20, -10% RH) conditions specified in JIS K 7100, and then the thermal conductivity was measured one week (7 days) after the production of the styrene-based resin extruded foam. (6) JIS flammability In accordance with JIS A 9521, a test piece having a thickness of 10 mm, a length of 200 mm, and a width of 25 mm was used to evaluate the flammability according to the following criteria. The produced styrene-based resin extrusion foam was cut into a test piece having the above dimensions, and the test piece was left to stand under the conditions of standard temperature condition Class 3 (23°C ± 5°C) and standard humidity condition Class 3 (50 + 20, -10% RH) specified in JIS K 7100. One week (7 days) after the production of the styrene-based resin extrusion foam, the test piece was used to evaluate the flammability. ○: Meets the criteria of "flame goes out within 3 seconds, there is no residual fuel, and the fire does not burn beyond the flammability limit indicator line." ×: Does not meet the above criteria.
[0101] (7) Oxygen index The measurement was performed according to the method specified in JIS K 7201:1999.
[0102] (8) Weight average molecular weight retention of foam (hereinafter abbreviated as "Mw retention") In order to evaluate the degree of resin deterioration due to the thermal history in the extruder, the weight average molecular weight Mw of the foam obtained after each number of recycling was determined by gel permeation chromatography according to the following procedure. a) Sample concentration: 2.5 mg / mL (solvent: chloroform) b) Equipment used: Waters e2695 c) Columns used: Shodex GPC-K-806M, two columns connected directly d) Measurement conditions: temperature; 40°C, solvent; chloroform, sample injection amount; 50 μL, flow rate; 1.0 mL / min, detection method; UV (254 nm), standard polystyrene; "Shodex STANDARD SM-105" manufactured by Showa Denko K.K. The weight average molecular weight Mw of the foam obtained after 5 recycling cycles was divided by the weight average molecular weight Mw of the foam obtained after 0 recycling cycles, and the value was evaluated as the Mw retention rate. 〇: Mw retention rate is 0.90 or more ×: Mw retention is less than 0.90
[0103] [Examples and Comparative Examples] For the examples and comparative examples, graphite and titanium oxide were added via masterbatches prepared according to the following procedures.
[0104] [Preparation of graphite master batch] In a Banbury mixer, 100 parts by weight of styrene resin B [manufactured by PS Japan Co., Ltd., 680; MFR 7.0 g / 10 min], which is a base resin, and 102 parts by weight of graphite [manufactured by Marutoyo Foundry Manufacturing Co., Ltd., M-885] and 2.0 parts by weight of ethylene bisstearic acid amide [manufactured by NOF Corp., Alflo H-50S] were put in a Banbury mixer, and melt-kneaded for 20 minutes without heating or cooling under a load of 5 kgf / cm2. At this time, the resin temperature was measured and found to be 190°C. The strand-shaped resin, which was supplied to a ruder and extruded at a discharge rate of 250 kg / hr through a die with small holes attached to the tip, was cooled and solidified in a water tank at 30°C, and then cut to obtain a master batch.
[0105] [Preparation of titanium oxide master batch] A Banbury mixer was charged with 100 parts by weight of styrene resin B [680, manufactured by PS Japan Co., Ltd.] as the base resin, and 154 parts by weight of titanium oxide [R-7E, manufactured by Sakai Chemical Industry Co., Ltd.] and 2.6 parts by weight of ethylene bisstearamide [Alflow H-50S, manufactured by NOF Corporation] per 100 parts by weight of styrene resin B, and the resulting mixture was mixed at 5 kgf / cm. 2The mixture was melt-kneaded for 20 minutes without heating or cooling under a load of 1000 g for 20 minutes. The resin temperature was measured and found to be 180° C. The strand-shaped resin was fed to a ruder and extruded through a die with small holes attached to the tip at a discharge rate of 250 kg / hr. The strand-shaped resin was cooled and solidified in a water bath at 30° C., and then cut into pieces to obtain a master batch.
[0106] Example 1 [Preparation of resin mixture] The materials (materials other than the foaming agent) shown in Table 1 were dry-blended in the ratio shown in Table 1 to obtain a resin mixture. This dry blend is abbreviated as [GP].
[0107] [Preparation of extruded foam] The obtained GP was fed at about 800 kg / hr to an extruder in which a single screw extruder (first extruder) with a diameter of 150 mm, a single screw extruder (second extruder) with a diameter of 200 mm, and a cooler were connected in series. The resin composition fed to the first extruder was heated to a resin temperature of about 240°C to melt or plasticize and knead, and a foaming agent (HFO-1234ze 2.0 parts by weight, isobutane 1.8 parts by weight, dimethyl ether 2.5 parts by weight, water 0.9 parts by weight per 100 parts by weight of the base resin) was injected into the resin composition near the tip of the first extruder. Thereafter, in the second extruder and cooler connected to the first extruder, the temperature of the resin composition was cooled to the foaming temperature shown in Table 1, and the resin composition was extruded and foamed into the atmosphere at the foaming pressure shown in Table 1 from a die (slit die) with a rectangular cross section and a thickness shown in Table 1 provided at the tip of the cooler, and then an extruded foam board with a cross-sectional shape of 60 mm thick x 1000 mm wide was obtained using a molding die installed in close contact with the die and a molding roll installed downstream of it, and cut to a thickness of 50 mm, width 910 mm x length 1820 mm with a cutter. The above foam was used as the foam for the 0th recycling.
[0108] [Production of recycled resin] The foam obtained was crushed by a crusher and the cut waste generated when it was cut to a specified size by a cutter, and fed to a single screw extruder with a diameter of 120 mm, heated to a resin temperature of about 230°C to melt or plasticize, kneaded, and then discharged from a die and pelletized by strand cutting under open vent conditions after removing the foaming agent remaining in the foam. The pellets are called [RP] (recycled styrene resin).
[0109] [Preparation of extruded foam containing recycled resin] A foam was obtained under the same conditions and operations as in the above [Preparation of extruded foam], except that the RP and GP obtained as above were fed in a weight ratio of 50:50 to an extruder consisting of a single screw extruder with a diameter of 150 mm, a single screw extruder with a diameter of 200 mm, and a cooler connected in series, at about 800 kg / hr. The foam obtained was used as the foam for the first recycling run. Thereafter, recycling was carried out five times by repeating the [Preparation of recycled resin] and [Preparation of extruded foam containing recycled resin]. The evaluation results of the obtained foam are shown in Table 1. (Examples 2 to 12) Extruded foams were obtained in the same manner as in Example 1, except that the production conditions were changed as shown in Table 1. The physical properties of the obtained extruded foams are shown in Table 1. The cross-sectional shape and the thickness, width, and length after cutting of the obtained extruded foams were the same as in Example 1.
[0110] (Comparative Examples 1 to 3) Extruded foams were obtained in the same manner as in Example 1, except that the production conditions were changed as shown in Table 2. The physical properties of the obtained extruded foams are shown in Table 2. The cross-sectional shape and the thickness, width, and length after cutting of the obtained extruded foams were the same as in Example 1.
[0111] [Table 1]
[0112] [Table 2]
[0113] As shown in Table 1, foams excellent in flame retardancy and Mw retention were obtained in Examples 1 to 12. On the other hand, as shown in Table 2, foams poor in flame retardancy and / or Mw retention were obtained in Comparative Examples 1 to 3. [Industrial Applicability]
[0114] The extruded styrene-based resin foam according to one embodiment of the present invention can be used, for example, as a heat insulating material, a sound absorbing material, a core material for a vacuum heat insulating material, a cushioning material, and a filler material.
Claims
1. A styrene-based resin extruded foam, which is a foam of a resin composition containing a polystyrene resin, a heat radiation inhibitor, a flame retardant, and a stabilizer, The resin composition comprises It contains recycled resin made by melting and kneading styrene-based resin extrusion foam. The flame retardant comprises one or more aliphatic bromine-containing polymers selected from the group consisting of brominated styrene-butadiene block copolymers, brominated styrene-butadiene random copolymers, brominated styrene-butadiene graft polymers, brominated butadiene polymers, and brominated epoxidized styrene-butadiene block copolymers; The stabilizer includes an epoxy compound, The composition contains 0.5 to 5.0 parts by weight of the heat radiation inhibitor and 0.5 to 10 parts by weight of the aliphatic bromine-containing polymer relative to 100 parts by weight of the polystyrene resin, The epoxy compound is contained in an amount of 21 to 50 parts by weight based on 100 parts by weight of the aliphatic bromine-containing polymer. Extruded styrene resin foam.
2. The resin composition further contains a phenol-based stabilizer and a phosphite-based stabilizer as the stabilizer, The phenol-based stabilizer is contained in an amount of 4 to 20 parts by weight, and the phosphite-based stabilizer is contained in an amount of 0 to 0.9 parts by weight, based on 100 parts by weight of the aliphatic bromine-containing polymer. The extruded styrene resin foam according to claim 1.
3. The styrene-based resin extruded foam described in claim 2, wherein the resin composition further contains, as the stabilizer, 20 parts by weight or less of a polyhydric alcohol partial ester which is a reaction product of dipentaerythritol and adipic acid per 100 parts by weight of the aliphatic bromine-containing polymer.
4. The styrene-based resin extruded foam according to claim 2 or 3, wherein the phosphite stabilizer comprises at least one selected from the group consisting of 3,9-bis(2,4-di-tert-butylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, and tetrakis(2,4-di-tert-butyl-5-methylphenyl)-4,4'-biphenylene diphosphonite.
5. The extruded styrene-based resin foam according to any one of claims 1 to 4, comprising, as the epoxy compound, at least one selected from the group consisting of bisphenol A diglycidyl ether type epoxy resins, cresol novolac type epoxy resins, and phenol novolac type epoxy resins.
6. The styrene-based resin extruded foam described in any one of claims 1 to 5, wherein the resin composition further contains a phosphate ester.
7. The extruded styrenic resin foam according to claim 6, wherein the phosphate ester is tetrakis(2,6-dimethylphenyl)-m-phenylene bisphosphate.
8. The styrene-based resin extruded foam described in any one of claims 1 to 7, wherein the resin composition further contains hydrofluoroolefin and / or hydrochlorofluoroolefin as a foaming agent.
9. The styrene-based resin extruded foam described in claim 8, wherein the total content of hydrofluoroolefin and hydrochlorofluoroolefin in the resin composition is 1.0 part by weight or more and 12.0 parts by weight or less per 100 parts by weight of the polystyrene resin.
10. The extruded styrene-based resin foam according to any one of claims 1 to 9, comprising graphite and / or titanium oxide as the heat radiation inhibitor.
11. The extruded styrene-based resin foam described in any one of claims 1 to 10, having a thermal conductivity of 0.0244 W / mK or less.
12. Density: 20 to 60 kg / m 3 The extruded styrene-based resin foam according to any one of claims 1 to 11.
13. A styrene-based resin extruded foam described in any one of claims 1 to 12, having a thickness of 10 mm or more and 150 mm or less.
Citation Information
Patent Citations
Foaming agents and compositions containing fluorinated olefins, and foaming methods
JP2008546892A
Extruded styrene resin foam and method for producing the same
JP2013221110A
Styrenic resin extrusion foam and method for producing the same
JP2019031636A
Styrene-based resin extrusion molding
JP2019094472A
Styrenic resin extrusion foamed body and manufacturing method thereof
JP2019108416A
